Canary in the coal mine: Lessons from the Jarrah Forest suggest long-term negative effects of phosphorus fertilizer on biodiverse restoration after surface mining - Daws, Matthew I.; Blackburn, Cameron; Standish, Rachel J.; Tibbett, Mark (Frontiers in Forests and Global Change, 2022)
Despite nutrient enrichment having widely reported negative impacts on biodiversity, fertiliser is routinely applied in post-mining restoration to enhance plant growth and establishment. Focusing on surface mine restoration (predominately bauxite and mineral sands), we outline the long-term negative impacts of fertiliser, particularly phosphorus fertiliser, on plant community composition, species richness, fire fuel loads, and belowground impacts on nutrient cycling. We draw from extensive research in south-western Australia and further afield, noting the geographical coincidence of surface mining, phosphorus impoverished soil and high plant biodiversity. We highlight the trade-offs between rapid plant-growth under fertilisation and the longer-term effects on plant communities and diversity. We note that the initial growth benefits of fertilisation may not persist in water-limited environments: resulting in unfertilised forests eventually matching fertilised forest growth throwing doubt on the premise that fertilisation is necessary at all.